2018
DOI: 10.1103/physrevd.98.104039
|View full text |Cite
|
Sign up to set email alerts
|

Differentially rotating neutron stars in scalar-tensor theories of gravity

Abstract: We present the first numerical models of differentially rotating stars in alternative theories of gravity. We chose a particular class of scalar-tensor theories of gravity that is indistinguishable from GR in the weak field regime but can lead to significant deviations when strong fields are considered. We show that the maximum mass that a differentially rotating neutron star can sustain increases significantly for scalarized solutions and such stars can reach larger angular momenta. In addition, the presence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 50 publications
(70 reference statements)
0
28
0
Order By: Relevance
“…For this reason, in the present paper we will present only the solutions with no zeros of the scalar field. We should note, that the Schwarzschild solutions is also unstable for black hole masses below the mass corresponding to the bifurcation point [37]. The points of bifurcation for different masses of the scalar field can be best observed in Fig.…”
Section: Spontaneously Scalarized Black Holesmentioning
confidence: 79%
See 1 more Smart Citation
“…For this reason, in the present paper we will present only the solutions with no zeros of the scalar field. We should note, that the Schwarzschild solutions is also unstable for black hole masses below the mass corresponding to the bifurcation point [37]. The points of bifurcation for different masses of the scalar field can be best observed in Fig.…”
Section: Spontaneously Scalarized Black Holesmentioning
confidence: 79%
“…In our numerical solutions we shall use β = 12 but similar results are observed for other values of β as well. We refer the reader to [37] for an extensive discussion of the influence of the parameter β on the properties of the scalarized solutions in the massless case. As we know from the massless scalar field case [28,37], for such coupling in addition to the Schwarzschild solution additional scalarized solutions branch off the GR one that can be labeled The value of the scalar field on the horizon versus the rescaled mass of the black hole for the exponential coupling function (19).…”
Section: Spontaneously Scalarized Black Holesmentioning
confidence: 99%
“…Consideration of the values smaller than the lower limit from the observations is justified because in the present study which is the first investigation of the scalarized FM neutron stars, we are interested on the effects of the coupling constant on the scalarization of these stars. In addition, the calculations with β < −4.5 in the massless case give the upper limit for the deviations from GR in the massive case [38]. We also calculate the maximum value of the coupling constant at which the spontaneous scalarization takes place in NFM and FM neutron stars.…”
Section: Formalismmentioning
confidence: 97%
“…These theories which include one or more scalar fields coupled to matter, predict scalar gravitational wave that can be detected by the laser interferometer [22,23]. These theories of gravity have been extensively applied to investigate the relativistic compact objects [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. It has been confirmed that a wide class of STTs passes the weak-field gravitational tests indicating nonperturbative strong-field deviations away from GR in neutron stars [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation